Influencia de la pandemia por covid-19 en el estado emocional de un adolescente de 13 años de la Unidad Educativa 23 de Junio del cantón Baba - Aguilar Candelario, Evelyn Yolanda (2021)
The present case study was carried out with the objective of Determining the influence of the virus (SARS-CoV2 -COVID 19) on the emotional state of a 13-year-old adolescent from the June 23 educational unit in Baba Canton. In this way, evaluation techniques such as medical history, Beck's depression test and the registry of thoughts and emotions were used, very important techniques to be able to reach the diagnosis for an F33.2 Recurrent depressive disorder, current severe episode without psychotic symptoms, in addition the adolescent shows distortion of thought, isolation, little concentration, loss of interest in activities, among others. These techniques allowed the objective set corresponding to the patient through a therapeutic plan which includes a cognitive restructuring procedure, aimed at modifying those thoughts that the patient presented during the psychological intervention. All this in order for the patient to overcome their problem and improve their quality of life, both personal and social. On the other hand, the commitment and collaboration of the adolescent during the sessions carried out in the psychological intervention is highlighted, resulting in a prognosis that benefits an emotional and social change.